Pengaruh Penguasaan Mata Kuliah Klasifikasi DDC terhadap Kemampuan Menentukan Notasi - Nur Afifah (Perpustakaan Nasional RI, 2022)
This study aims to determine how the mastery of the DDC classification subject has on the abilities of the students of the 2017-2019 Library Science study program in determining the DDC notation. This study took a sample of 99 students of the Library Science study program at UIN Raden Fatah Palembang in 2017-2019. The type of research used is descriptive quantitative. Methods of data collection in this study in the form of questionnaires and documentation.The data processing technique in this research is to analyze the data using the grand mean formula. The results of the analysis show that the average total score of mastery of DDC classification courses is 0.61 which can be categorized as high because it is in the 0.60-0.80 interval. Meanwhile, the ability to determine notation is also known by performing calculations using the grand mean formula, the results show that the average total value of the ability to determine notation is 0.62 which can be categorized as high because it is in the 0.60-0.80 interval. Furthermore, based on the analysis using simple linear regression, the result of the coefficient of determination (R2) of 0.807 or 80.7% the ability to determine notation is influenced by the mastery of the DDC classification course and based on the results of hypothesis testing that it is known that the hypothesis or H1 is accepted because tcount ttable (20,113 1.66071) which states that there is an influence of mastery of the DDC classification course on the ability to determine notation.